Enzyme inactivation induced by thermal stabilization in highland barley and impact on lipid oxidation and aroma profiles - Zheng, Qianna; Wang, Zheng; Xiong, Feiyang; Zhang, Guoquan (Frontiers in Nutrition, 2023)
Thermal stabilization is efficient for slowing lipid degradation and prolonging the shelf life of highland barley, but the impacts of different thermal stabilized treatments on highland barley and possible chemical reactions remain unclear. The effects of thermal stabilization treatments (bake, far-infrared, fry, microwave and steam) on the enzymes, lipids and aroma profiles of highland barley flour (HBF) were investigated in this study. Thermal stabilization significantly decreased the contents of ash and GABA. Baked HBF exhibited the lowest fatty acid value and peroxide value. Untreated HBF had higher lipase and lipoxygenase activities and fried mostly inactivated these enzymes. All thermal stabilization treatments increased the catalase activities and fried showed the higher level. Thus, fried might be an effective method to stabilize the HBF. The high temperatures during stabilizing triggered the complex reactions, leading to the loss of some volatile compounds, and in the meantime the formation of others such as furans and aldehydes. These productions contributed to the unique aroma profiles of different HBFs. Furthermore, a chemometric approach was used to analyze the changes of thermal stabilized treated HBFs and to identity six key volatile compounds, which provided important knowledge on possible chemical reactions caused by thermal stabilization. Overall, these results provide the theoretical basis for the wider application of thermal stabilization technologies in highland barley processing.